Sea Ice Concentration Manifestation in Radar Signal at Low Incidence Angles Depending on Wind Speed - Maria Panfilova; Vladimir Karaev (Remote Sensing)
In previous studies, the possibilities of Ku-band radar measurements at low incidence angles were investigated for the task of sea ice detection. In this paper, the sensitivity of normalized radar cross-section to sea ice concentration is investigated at various wind conditions. The data of Ku-band radar onboard GPM satellite are used, and the sea ice concentration product from Bremen University website is implemented as reference data and the information on wind speed from reanalysis was applied. Simple analytical parameterization was obtained for the normalized radar cross-section depending on sea ice concentration and wind speed for various incidence angles using the regression method. The threshold behavior of the normalized radar cross-section with increase in wind speed was revealed and preferable wind conditions for sea ice concentration detection were identified.